An explanation of the observation of pulsing hiss at low latitude - Singh, A.K.; Singh, Rajesh; Singh, Kalpana; Singh, R.P. (My University, 2008)
In this paper we report pulsing hiss emissions observed at the low latitude station, Jammu (geomag. lat. 22°26′N, L = 1.17) in which intensity decreases with the increase in frequency. The entire dynamic spectra contain somewhat irregular structure. To explain these we propose that the hiss emissions are generated through Doppler-shifted cyclotron interactions near the equator and propagate to the earth in the whistler-mode. Further, ULF waves present in the generation region modulate the intensity of the emission resulting in the pulsing nature. The growth rates are computed and discussed in the light of recent works.
Keywords: VLF Emissions; Hiss emission; Whistler-mode waves; Magnetospheric physics; Low latitude; ULF waves